2022
DOI: 10.1002/anie.202117063
|View full text |Cite
|
Sign up to set email alerts
|

An Isolable Vinylidene ortho‐Quinone Methide: Synthesis, Structure and Reactivity

Abstract: Commonly, an elusive intermediate is generated from a precursor and then trapped and consumed in a reaction. Vinylidene ortho-quinone methides (VQMs) have been demonstrated as transient axially chiral intermediates in asymmetric catalysis due to their orthogonal π-bonds forming an allene motif. The current understanding of VQMs is primarily based on timeresolved absorption, trapping experiments and computational studies. Herein, we report the first isolation and comprehensive characterization of a VQM, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Another transformations for the synthesis of allenones include an anionic Oxy‐Cope rearrangement/oxygenation, [54] a vinylidene ortho‐quinone methide synthesis, [55] or a recent approach to a List‐Lerner‐Barbas aldol reaction including examples of allenones in broader scopes [56] …”
Section: Synthesis Of Allenonesmentioning
confidence: 99%
“…Another transformations for the synthesis of allenones include an anionic Oxy‐Cope rearrangement/oxygenation, [54] a vinylidene ortho‐quinone methide synthesis, [55] or a recent approach to a List‐Lerner‐Barbas aldol reaction including examples of allenones in broader scopes [56] …”
Section: Synthesis Of Allenonesmentioning
confidence: 99%
“…After adjusting the structure of VQM precursors and tuning the reaction conditions, the isolation and characterization of a VQM intermediate were achieved recently by our group. 25 The tetra-substituted VQM was successfully isolated as a yellow solid and exhibited good thermal stability (Scheme 2c). Structural characterization was achieved including crystallographic analysis; the X-ray structure demonstrated that the neutral nonaromatic representation was the major resonance structure in the solid state.…”
Section: Accounts Of Chemical Researchmentioning
confidence: 99%
“…After adjusting the structure of VQM precursors and tuning the reaction conditions, the isolation and characterization of a VQM intermediate were achieved recently by our group . The tetra-substituted VQM was successfully isolated as a yellow solid and exhibited good thermal stability (Scheme c).…”
Section: Discovery and Identification Of Vinylidene Ortho-quinone Met...mentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, we reported the isolation of stable VQM with a bulky phenylsulfonyl group on the allene motif . The isolation and characterization of the VQM intermediate provided an unprecedented opportunity to directly interrogate the two sequential mechanistic events in VQM-involved reactions.…”
mentioning
confidence: 99%